Análise da política de concessão de recursos hídricos no município de Manaus - Carvalhosa, Wallace Ferreira (2016)
This dissertation is subject to analysis of the privatization of the supply of water resources in the face of the guarantee of fundamental human right to access to water, providing examples both in the global context and the national, performing especially a reflection within the city of Manaus. The Brazil enacted Law 9,433 / 97 within a scenario of privatization and concerns about shortages, quantitative and qualitative water when the water begins to acquire economic value. In fact, the shortage legitimizes the collection of water resources and Brazil attracts the interest of multinational corporations, supported by the World Bank, the International Monetary Fund and the World Trade Organization, which will seeping in providing pickup and delivery services water, in comparison with the fundamental right of access to water, an inalienable right. As methodological procedure divided this work into five chapters. In the first, it contained a discussion of the environmental and economic aspects of water, as its importance, its multiple uses, in addition to the pictures of scarcity, pollution and conflicts over water. The next chapter analyzes the legal aspects of water, bringing the principles applied to the right to water, pointing to the laws applied to water. The third chapter deals with the detailed study of the policy of privatization of water supply services in its global and national context, analyzing the time the water becomes interpreted as a commodity as well as the influence of the World Bank and International Monetary Fund corporative control of water through loans to multinational enterprises in the sector. The fifth chapter deals with the privatization process under the law of the city of Manaus, analyzing the provision of water supplies to large private multinational group services, resulting in a Parliamentary Commission of Inquiry and a public civil action to investigate the irregularities in the process of granting the public service of water supply. The struggle for access and control of water by private interests is considered in this work, as an expression of conflict, before the opening of the private concession to provide services in the water supply and sanitation area